A cross‐sectional survey on principal investigators' clinical research knowledge in Japan - Miwa Sekine; Koshi Kataoka; Yuji Nishizaki; Kotone Matsuyama; Toshiaki Otsuka; Kensuke Sato; Mayumi Idei; Shoji Sanada (Wiley, 2023)
Abstract Principal investigators (PIs) play a key role in clinical research, and must thus understand the role of clinical research support staff to conduct successful and appropriate clinical research. This study evaluates clinical research capabilities by examining the clinical research knowledge of PIs and clinical research support staff. The participants of this cross‐sectional study were academic researchers and clinical research support staff from Japanese universities and research institutions. The participants comprised of 54 respondents, among whom 36 were PIs (physicians) and 18 were clinical research support staff. A self‐administered electronic survey was created and evaluated by experts, with 50 knowledge items. Mann-Whitney U tests were used to determine the significance of the differences in knowledge between clinical research support staff and PIs. We compared the correct answer rate of clinical research support staff and PIs for each knowledge category and observed that the clinical research support staff scored significantly higher than the PIs in all aspects of clinical research knowledge sections, including total score. Our findings showed that PIs did not have the same amount of clinical research knowledge as the clinical research support staff. Clinical research knowledge is essential for investigators, especially PIs, to protect patients and promote medical breakthroughs. Thus, more accessible clinical research education and mandatory knowledge testing will allow PIs to lead successful clinical research and further the level of medical research in Japan.